Menelusuri Jejak Misi Teologi Interkultural dalam Pelayanan Gereja Protestan Indonesia Donggala (GPID) (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
Culture is a contemporary issue that has received the attention of the Church in mission. The GPID is a mainstream church with ethnic and ethnic diversity. The author uses the theory of Robert J. Schreiter to bring together the diverse cultures of the mission approach. This type of research is library research and the method used is a qualitative analysis of ethnic and ethnic diversity in carrying out missions. In carrying out a mission, there are several things that need to be considered by the church in the context of religion and culture, the context of poverty, the context of injustice and Intercultural Theology are things that need to be done in the context of missions in conducting meetings with religion, theology, and with other churches.